Hosea 6:6 and identity formation in Matthew - F. P. Viljoen (Acta Theologica)
Matthew uses Hos. 6:6 in two scenes of conflict between Jesus and the Pharisees. He defines the differences between Jesus and the Pharisees in terms of adherence to the Law with focus on the mercy that God desires. Matthew depicts Jesus as one who teaches and enacts Hos. 6:6 in continuity with the original prophetic intention of this statement. Jesus teaches by example by enacting mercy towards the marginalized and people in need. He loves the way Hosea announces that God intends his people to love. Jesus Himself becomes the presence and source of mercy. Jesus forms the central focus and prototype of the Matthean community. The community should follow his example.